Dampak Program Pemulihan Layanan terhadap Loyalitas Pelanggan di Industri Logistik - Suryani, Wan; Amelia, Wan Rizca; Iriantini, Dwi Bhakti (Universitas Medan Area, 2024)
This research discusses the impact of service recovery programs on customer loyalty in the logistics industry with a focus on marketing public relations, service recovery and customer loyalty. In the context of an increasingly competitive logistics industry, maintaining customer loyalty is crucial for the company's business continuity. A service recovery program is an important strategy to carry out. A service recovery program is an effort to resolve customer problems or dissatisfaction by providing compensation or satisfactory solutions, so as to improve the relationship between the company and customers who experience problems. This research used a purposive sampling method with a sample of 400 respondents. The research results show that marketing public relations and service recovery have a positive effect on customer loyalty. The conclusion of this research is that marketing, public relations, and service recovery have a high relationship with customer loyalty at PT. Nugraha Ekakurir (JNE) route in Medan